ANALISA VISUAL DARI ELEMEN PERMAINAN KARTU ‘THE ART OF BATIK’ - Brian Alvin Hananto; Jennifer Audiah (Jurnal Bahasa Rupa, 2019)
Card games have become a common object that is used not only for playing but also to inform and teach several things through its gameplay. ‘The Art of Batik’ was a card game designed by Adhit WP, illustrated by M. Bahroen and published by Hompimpa! Games. The card game wanted to teach its players about a simplified process and steps of producing Batik with its gameplay. Unfortunately, the game is considered hard to understand and it fails to inform the intended messages to its players. The author tries to study more about the issue and the game’s element and rules, the author also examines the visuals and interface of the game. The author concludes that the main issue is found on the visual of ‘The Art of Batik’ card game. The cards have poor information arrangement and hierarchy, which can be properly addressed by reconsidering the layout of the pieces of information. From this conclusion, the author suggests that a redesign of ‘The Art of Batik’ can be executed based on the author's foundings so that the game can be more effectively played and easier to understand.